PPAR-γ Regulates Carnitine Homeostasis and Mitochondrial Function in a Lamb Model of Increased Pulmonary Blood Flow - Sharma, Shruti (Public Library of Science, 2012)
OBJECTIVE: Carnitine homeostasis is disrupted in lambs with endothelial dysfunction secondary to increased pulmonary blood flow (Shunt). Our recent studies have also indicated that the disruption in carnitine homeostasis correlates with a decrease in PPAR-γ expression in Shunt lambs. Thus, this study was carried out to determine if there is a causal link between loss of PPAR-γ signaling and carnitine dysfunction, and whether the PPAR-γ agonist, rosiglitazone preserves carnitine homeostasis in Shunt lambs. METHODS AND RESULTS: siRNA-mediated PPAR-γ knockdown significantly reduced carnitine palmitoyltransferases 1 and 2 (CPT1 and 2) and carnitine acetyltransferase (CrAT) protein levels. This decrease in carnitine regulatory proteins resulted in a disruption in carnitine homeostasis and induced mitochondrial dysfunction, as determined by a reduction in cellular ATP levels. In turn, the decrease in cellular ATP attenuated NO signaling through a reduction in eNOS/Hsp90 interactions and enhanced eNOS uncoupling. In vivo, rosiglitazone treatment preserved carnitine homeostasis and attenuated the development of mitochondrial dysfunction in Shunt lambs maintaining ATP levels. This in turn preserved eNOS/Hsp90 interactions and NO signaling. CONCLUSION: Our study indicates that PPAR-γ signaling plays an important role in maintaining mitochondrial function through the regulation of carnitine homeostasis both in vitro and in vivo. Further, it identifies a new mechanism by which PPAR-γ regulates NO signaling through Hsp90. Thus, PPAR-γ agonists may have therapeutic potential in preventing the endothelial dysfunction in children with increased pulmonary blood flow.